The coupling effect of gas-phase chemistry and surface reactions on oxygen permeation and fuel conversion in ITM reactors - Hong, Jongsup; Kirchen, Patrick; Ghoniem, Ahmed F. (ELSEVIER SCIENCE BV, 2015)
The effect or the coupling between heterogeneous catalytic reactions supported by an ion transport membrane (ITIVI) and gas-phase chemistry on fuel conversion and oxygen permeation in ITM reactors is examined. In ITM reactors, thermochemical reactions take place in the gas-phase and On the membrane surface, both of which interact with oxygen permeation. However, this coupling between gas-phase and surface chemistry has not been examined in detail. In this study, a parametric analysis using numerical simulations is conducted to investigate this coupling and its impact on fuel conversion and oxygen permeation rates. A thermochemical model that incorporates heterogeneous chemistry on the membrane surface and detailed chemical kinetics in the gas-phase is used. Results show that fuel conversion and oxygen permeation are strongly influenced by the simultaneous action of both chemistries. It is shown that the coupling somewhat suppresses the gas-phase kinetics and reduces fuel conversion, both attributed to extensive thermal energy transfer towards the membrane which conducts it to the air side and radiates to the reactor walls. The reaction pathway and products, in the form of syngas and C2 hydrocarbons, are also affected. In addition, the operating regimes of ITM reactors in which heterogeneous- or/and homogeneous-phase reactions predominantly contribute to fuel conversion and oxygen permeation are elucidated. (C) 2015 Elsevier By. All rights reserved,
Keywords: ION-TRANSPORT MEMBRANE; DENSE CERAMIC MEMBRANES; PARTIAL OXIDATION; METHANE CONVERSION; PEROVSKITE MEMBRANES; CHEMICAL-REACTIONS; SYNGAS; COMBUSTION; SIMULATION; EXCHANGE